1968
DOI: 10.1203/00006450-196803000-00009
|View full text |Cite
|
Sign up to set email alerts
|

The Plasma Aminogram. I. Influence of the Level of Protein Intake and a Comparison of Whole Protein and Amino Acid Diets

Abstract: ExtractThe changes in plasma aminogram prcduced by variations in level of protein intake provided either as whole protein or a mixture of amino acids were studied. Controls were 29 normal infants, one to three months of age, fed a standard evaporated milk formula providing 3 to 3.5 g/kg/day of protein (fig. 1 and table II). Results obtained with the lowest protein intake (1.1 g/kg/day) are illustrated in figure 2 and presented in table III. Alterations in the plasma aminogram are noted as early as two days aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
0

Year Published

1969
1969
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(42 citation statements)
references
References 9 publications
2
40
0
Order By: Relevance
“…The higher nitrogen intake in the HM-Pr group was associated with higher prefeeding plasma amino acid concentrations. This is not surprising, as there is a well-known correlation between plasma amino acid levels and protein intake (22,23). Plasma amino acid levels taken immediately before a feed have been recommended for screening of any diet-induced, step-by-step accumulation of several amino acids, whereas postprandial amino acid measurements are a useful means of testing the infant's ability to handle amino acid loads in feeds (24).…”
Section: Discussionmentioning
confidence: 99%
“…The higher nitrogen intake in the HM-Pr group was associated with higher prefeeding plasma amino acid concentrations. This is not surprising, as there is a well-known correlation between plasma amino acid levels and protein intake (22,23). Plasma amino acid levels taken immediately before a feed have been recommended for screening of any diet-induced, step-by-step accumulation of several amino acids, whereas postprandial amino acid measurements are a useful means of testing the infant's ability to handle amino acid loads in feeds (24).…”
Section: Discussionmentioning
confidence: 99%
“…The homeostasis of free amino acids in the plasma changes characteristically in ex perimental protein undemutrition (low in take of nitrogen) [1,5,34,36], This change is also seen in the clinical syndrome of protein deficiency [6,10,17,39,40] and PEM [6,13,15,17,18,31,32,37], There are only a few studies on homeosta sis of plasma-free amino acids in newborn infants with retarded intrauterine growth. Lindblad [19,20] has reported changes in amino acid levels during the first hours of extrauterine life in children who were under weight and short-for-gestational age as a re sult of hypertension in pregnancy and Mestian et al [26] have shown the postnatal changes in some amino acid ratios in preterm infants (PTI) and SFD infants.…”
mentioning
confidence: 99%
“…The influence of protein intake on the plasma aminogram has been studied in adults [35,38] and children [2,31,32] but little is known about the changes in urinary amino acid excretion. In the current study, this has been investi gated in 14 children.…”
mentioning
confidence: 99%